Peranan Motivasi Dalam Meningkatkan Kinerja Tenaga Kependidikan Fakultas Ilmu Sosial dan Politik Universitas Sam Ratulangi - Pendong, Yemita Listiana; Dengo, Salmin; Plangiten, Novva (Sam Ratulangi University, 2015)
Abstract: Currently there is no doubt that in the era of globalization there is no doubt have demanded a lot of change, improvement and increased in various fields. If connected to the human resources needs to be an increase in the quality of labor and the ability to be able to independently and compete. Among one of the aspects relating to human resources, which must be considered by the agency is working motivation of employees (employees) is the willingness of employees to concentrate all its efforts for the agency.Motivation is increasingly important because of the leadership of the subordinates to share the work done well and directed to the goals previously set. Leadership in motivating employees should realize that humans have a willingness to work hard in the hope he will be able to meet the needs and desires of his work. In carrying out its work, the employee does not carry out all the work yourself, but sometimes it takes a good cooperation among employees in completing a job. In this case, leaders must encourage and stimulate the motion (working willingness) employee to perform a job that was his duty so that they are motivated to work as best as possible and be able to improve the productivity of their labor. It is worth noting because human labor as a man who can not be driven away, but living beings who have feelings, needs, desires and mindset alone.In improving organizational performance in a wide range of internal and external aspects, in other words Motivation determined on their relationships with the various aspects that come from individual employees themselves, as well as from outside the individual. This study found that the motivation factor, turns out to have a close relationship and significant impact on the workings of employees / educators. Therefore disimpulakan that, the role of motivation to have a significant role in the performance of an organization meningkatakn is the driving force of the organization.Keywords: Role, Motivation, and Performance